Different Types of Ventilation Systems of Munitions - Adam WIŚNIEWSKI (Różne typy systemów wentylacyjnych amunicji, 2017)
In the article it is presented the guideline and requirements for construction and technology designing of munition, that allows mitigation and decreasing after effects of stimuli impacting the Insensitive Munition (IM), used in military equipment, i.e. in case of pressure and temperature increase during fire, fast and slow heating, sympathetic detonation, perforation of the munition by a projectile, a fragment or a shaped charge jet. The construction of the IM munition is specified with the use of barriers, ventilation/deaeration of the munition case and double-purpose technology. The features of the active and passive/inert ventilation systems of the IM munition are presented, examples of absorbing energy materials and structure of covers/barriers of a „sandwich” type. Depending on the IM classes of threats and different representative standards and one metric of munition response and technology maturity, there are different consequences of detonation, explosion, deflagration/propulsion, burn, not sustained reaction, etc. observed. Some examples are presented with the use of the shaped-memory alloys or polymers in the Insensitive Munition.
Keywords: Konstrukcja amunicji artyleryjskiej